Rumah Belajar Siswa pada Masa Pandemi Covid-19 di kelurahan Mangalli Kabupaten Gowa - Ilham Kamaruddin; Nur Indah Atifah Anwar; Andi Annisa Triana Amir; Annisa Annisa; Jurana Jurana (Yayasan Literasi Sains Indonesia, 2022)
The existence of the Covid-19 Pandemic which forced the implementation of the Large-Scale Social Restriction (PSBB) policy was a shock effect for all of us. each through online learning. However, with this change, there are not a few obstacles, ranging from difficulties in getting an internet network to declining student interest in learning. It was from this that KKN-PPL UNM created a work program called Rumah Belajar which facilitates students, especially students of SMP Negeri 1 Pallanggga, to study together in a more interesting way and pay attention to health protocols. The methods of activities carried out in this program are: (1) Planning/preparation, (2) Observation, (3) Implementation, and (4) Evaluation. The results of the implementation of the Learning House program are very significant. Students' interest in learning increases so that they are more active in learning. This can be seen because several KKN-PPL UNM students in the Mangalli sub-district teach at SMPN 1 Pallangga, which is a learning house participating school.